Impact of supply chain management strategies on the performance indicators of small and medium-sized businesses - Nail Israfilov; Ildar Ablaev; Almira Seisinbinova; Tatyana Sakulyeva (International Journal of Supply Chain Management, 2020)
Abstract—The study considers the impact of supply chain management strategies on the performance of small and medium-sized businesses. It is shown that developed 4PL operators are economic integrators of countries dominated by small and medium-sized enterprises. The study deals with the data of the Federal Republic of Germany, China, the Republic of Kazakhstan, and the Russian Federation. The research hypothesis has been statistically confirmed: higher-level business models of supply chain management (for example, 4PL) are used in countries where there are significant investments in information and communication technologies. This positively affects the turnover of small and medium-sized enterprises. Logistics providers are supply chain integrators. It has been established that the higher the share of small and medium-sized businesses in the country's economy, the more developed the supply chain management system is. It has been shown that developed small and medium-sized businesses are integrated into a single management system with the help of 4PL operators; this makes it possible to increase the efficiency of both small and medium-sized enterprises and logistics operators. The scheme for increasing the efficiency of small and medium-sized businesses based on e-logistics has been presented.